Adaptation As A Process Of Translation. One Thousand And Nights Of GALLAND (El-Wahat Journal for Research and Studies, 2020)
Translation is considered as a linguistic ¸literary¸ and cultural process. Through translation¸ the great parts cultural features are transmitted from the original text to the translated one. The translator tries to cover some gaps by depending on adaptation via using notes ¸for example, and other techniques. In this article, we suggest the techniques used by GALLAND to translate the work “one thousand and one nights” for covering gaps and transmitting ideas.Keywords: translation, culture, adaptation, omission, addition, equivalent, substitution.